THE AUTHORITY RATIONALIZATION PHILOSOPHY OF THE INDONESIA COMPETITION COMMISSION: The Due Process of Law and Maqashid Sharia Perspectives - Noer Yasin (Jurisdictie: Jurnal Hukum dan Syariah, 2022)
The Indonesia Competition Commission (ICC) is a super body institution in enforcing business competition law in Indonesia. There are three subsystems of authority in the said law, namely the authority to investigate and observe, the authority to prosecute and the authority to adjudicate. The ICC is full of conflicts of interest in performing its functions, thus, impartiality is not an easy task. This is normative research with statutory and conceptual approaches. The primary, secondary, and tertiary legal materials were obtained through literature study and analyzed using extensive interpretation. The research focus is, first, rationalization in the due process of law perspective guarantees the impartiality of the ICC in executing its authority. Second, in the maqashid sharia perspective, ICC can realize justice and protect citizens’ property. In the second perspective, this rationalization is included at the primary level by separating the prosecution and the adjudication authorities. The government should provide a clear policy so the ICC stands as a prosecution agency with more authority to conduct a search to obtain the needed evidence. Meanwhile, the authority to adjudicate is on the Commercial Court, a special court in the General Court. This article contributes thoughts on Business Competition Law and the authority of the KPPU in the legal process and the perspective of Maqashid sharia.Komisi Pengawas Persaingan Usaha merupakan lembaga superbody dalam menegakkan hukum persaingan usaha di Indonesia. Dalam hukum tersebut, terdapat tiga subsistem kewenangan, yaitu kewenangan penyelidikan dan penyidikan, kewenangan penuntutan, dan kewenangan mengadili. KPPU sarat dengan konflik kepentingan dalam menjalankan fungsinya, karenanya, imparsialitas sulit ditegakkan. Artikel ini merupakan penelitian normatif dengan pendekatan perundang-undangan dan konseptual. Bahan hukum primer, sekunder dan tersier diperoleh melalui studi kepustakaan dan dianalisis menggunakan penafsiran ekstensif. Fokus penelitian, pertama, rasionalisasi dalam perspektif due process of law menjamin imparsialitas KPPU dalam melaksanakan kewenangannya. Kedua, dalam perspektif maqashid syariah, KPPU dapat mewujudkan keadilan dan perlindungan harta benda warga negara. Dalam perspektif maqashid syariah, rasionalisasi ini masuk pada jenjang primer dengan memisahkan kewenangan penuntutan dan mengadili. Hendaknya pemerintah dapat memberikan kebijakan yang jelas agar KPPU berdiri sebagai lembaga penuntut dengan penambahan kewenangan untuk melakukan penggeledahan dalam upaya mendapatkan bukti-bukti yang dibutuhkan. Sedangkan, kewenangan mengadili ada pada Pengadilan Niaga yang merupakan pengadilan khusus dalam Pengadilan Umum. Artikel ini memberikan kontribusi pemikiran mengenai Hukum Persaingan Usaha serta kewenangan KPPU dalam proses hukum dan perspektif Maqashid sharia.